Multiscale time irreversibility: Is it useful in the analysis of human gait?. (January 2018) - Naranjo Orellana, J.; Sanchez Sixto, A.; De La Cruz Torres, B.; Sarabia Cachadiña, E.; Floria Martín, P.; Berral de la Rosa, F.J.
Abstract: Purpose: To analyze the complexity of the gait through the measurement of Multiscale Time Irreversibility in accelerometry signals obtained at the hip of healthy subjects and patients with intermittent claudication in order to differentiate the two situations. Methods: Ten healthy elderly subjects (age 60.2 ± 4.8 years; height 173.6 ± 6.6 cm; weight 88.9 ± 11.3 kg); and 12 patients with peripheral arterial disease (age 63.1 ± 5.4 years, height 168.6 ± 6.5 cm; weight 81.2 ± 15.9 kg) walked at a comfortable, freely-chosen pace for 10 min in an open circuit wearing a triaxial accelerometer on each hip. The Asymmetry Index was calculated (scales 1–20) from the accelerometry series on the axes X, Y and Z for each hip using the simplified algorithm proposed by M. Costa. Results: A lower asymmetry can be seen in the group of patients on the Y axis of both legs with respect to the control group (p = 0.001). Comparing one leg with the other, only the patients showed a difference on the Z axis (p = 0.04) with less asymmetry in the claudicant leg (0.29 ± 0.15 vs. 0.55  ± 0.49). Conclusions: The analysis of Multiscale Time Irreversibility through the Asymmetry Index is useful for the study of human gait and can reveal behavior that allows pathological situations to be distinguished.